COMPONENTS OF FUTURE BIOLOGY TEACHER’S TERMINOLOGICAL SYSTEM (EDUCATION IN THE 21ST CENTURY, 2023)
Professional and terminology competence is an integral part of the future teacher’sprofessional competence. The correctness, logic, appropriateness of the use of professional termsare distinguishes a competent teacher. After all, the term is a unified international designation of acertain object, phenomenon, process and provides informative speech, adequate perception of thebasic meaning. The biological terminology system include a nomenclature subsystem. Acompetent biology teacher in the course of his professional activity operates with both terms andnomens, which form the basis of the biological nomenclature. The purpose of the research is toidentify the role and possibility of step-by-step study of terminological elements, nomens,eponyms and acronyms during the terminological professional training of a biology teacher. Themain components of future biology teacher’s terminology system are indicated. The characteristicand classification of term elements, nomens, eponyms, acronyms are given. As a result oftheoretical analysis and testing of the method of formation of professional and terminologicalcompetence of future biology teachers professional training it is established: 1) the effectiveness ofterminological training of students is ensured by consistency and regularity; 2) the optimal stepby-step sequence of learning of biological terminology and nomenclature systems can beexpressed in the form of a chain "terminoelement + nomen – acronym – eponym". An accessible,fairly simple and effective form of terminological work is the compilation of a thematicterminological dictionary, which can be presented in both handwritten and electronic form andincludes short and extended definitions of terms and (or) terminological elements. One of the maintasks of future teachers terminological training is to study the semantics and etymology of terms(including eponyms and acronyms) and nomens, which are based on Latin. The formation of anactive individual terminological dictionary of a student determines the further successful masteringthe disciplines of professional training, understanding international scientific terminology andbinary nomenclature. Mastering the complex knowledge of semantics and etymology of Greco-Latin terminoelements develops logic, enhances language culture and helps to expand theworldview of a biology student.
Keywords: professional and terminological competence; terminology; nomenclature; term; nomen; eponym; acronym; professional training; future biology teacher.